ADMM-Plus: Can It Do “CUES” in the South China Sea? - Tan, See Seng (2017)
The ADMM-Plus should jointly undertake a multilateral exercise that would test and illustrate the application of the Code of Unplanned Encounters at Sea (CUES) in the South China Sea.